2001
DOI: 10.1207/s15327590ijhc1304_05
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluator Effect: A Chilling Fact About Usability Evaluation Methods

Abstract: Computer professionals have a need for robust, easy-to-use usability evaluation methods (UEMs) to help them systematically improve the usability of computer artifacts. However, cognitive walkthrough (CW), heuristic evaluation (HE), and thinking-aloud study (TA)-3 of the most widely used UEMs-suffer from a substantial evaluator effect in that multiple evaluators evaluating the same interface with the same UEM detect markedly different sets of problems. A review of 11 studies of these 3 UEMs reveals that the eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
106
2
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(112 citation statements)
references
References 26 publications
3
106
2
1
Order By: Relevance
“…While it is possible to perform a test to determine quantitative measures like efficiency, effectiveness, and satisfaction (ISO, 1998), another common goal is to identify specific parts of a system that cause users trouble (Hertzum and Jacobsen, 2001) in order to improve the system. This is often called formative testing (Barnum, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is possible to perform a test to determine quantitative measures like efficiency, effectiveness, and satisfaction (ISO, 1998), another common goal is to identify specific parts of a system that cause users trouble (Hertzum and Jacobsen, 2001) in order to improve the system. This is often called formative testing (Barnum, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, research has shown that the set of identified problems depends both on the users taking part in the user test (Nielsen, 1994), and the evaluators analysing the data (Jacobsen, 1999;Hertzum and Jacobsen, 2001). Usually, products are tested with users who use these products for the first time, but it could be expected that there are differences in users' behaviour when they have become more familiar with a product.…”
Section: Introductionmentioning
confidence: 99%
“…This may be explained as an evaluator effect, since the Nielsen heuristics rating involves interpretation of the heuristics (Hertzum and Jacobsen, 2003). It is interesting to note that customer ratings, time on task measurements and mental workload measurements yield the same results, while the Nielsen heuristics rating does not.…”
Section: Layoutmentioning
confidence: 92%
“…It is interesting to note that customer ratings, time on task measurements and mental workload measurements yield the same results, while the Nielsen heuristics rating does not. The latter has also been questioned in terms of the type of problems that it detects (Wixon, 2003) and of evaluator effects (Hertzum and Jacobsen, 2003;Jeffries and Desurvire, 1992;Ling and Salvendy, 2009).…”
Section: Layoutmentioning
confidence: 99%
See 1 more Smart Citation